DEVELOPMENT OF A SYSTEM FOR PROTECTING THE RIGHTS OF WAR CRIMES VICTIMS IN UKRAINE: IMPLEMENTATION OF EUROPEAN UNION STANDARDS - Chystiakova, Yuliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Objective: to analyze existing and new elements of victim support systems in Ukraine, while deliberately excluding the study of their procedural rights; to determine the impact of the implementation of EU law standards on the regulation of these legal relations. Research methods: general scientific methods: induction, deduction, analysis and synthesis, generalization, comparative law. Results: it has been established that Ukraine is in the early stages of building a victim support system, and one of the key achievements is the creation of the Coordination Center for Victim and Witness Support, a specialized unit within the Prosecutor General’s Office. It has been proven that by giving priority to war crimes and international crimes, Ukraine is trying to solve the problem of delays in support measures that should have been introduced back in 2014. It has been justified that at the EU level, the fundamental framework for victims’ rights is provided by Directive 2012/29/EU (establishing minimum standards on the rights, support, and protection of victims of crime) and Directive 2004/80/EU (on compensation to victims of crime). The article identifies priority provisions for bringing Ukrainian legislation into line with these supranational norms and emphasizes the need to improve legislation in order to create a comprehensive and effective system for the protection of victims. Discussion: it has been found that the protection of victims’ rights is a constantly relevant issue in any legal system, obliging states and international organizations to respond quickly to crimes not only by punishing offenders, but also by restoring the rights of victims as much as possible through effective mechanisms. However, in practice, these mechanisms face significant obstacles, as many legal norms remain declarative and are not comprehensive. This problem is even more acute for victims of international crimes, the serious consequences of which require coordinated, specialized efforts, as is evident from the ongoing war in Ukraine. It has been concluded that the implementation of a victim-oriented approach in criminal proceedings is extremely important. This will allow us to focus not only on their procedural rights, but also on other equally important issues: legal, psychological, medical, and other forms of assistance. Harmonizing national legislation with EU standards should be an effective tool in this regard.